Pengaruh Kepuasan Kerja, Pengembangan Karir Dan Lingkungan Kerja Non Fisik Terhadap Retensi Karyawan Pada Pt. Bali Utama Cakrawala Kuta-Bali - Ayu Putu Nina Novyantari; Dewiwati Sujadi (Universitas Triatma Mulya, 2024)
Employee retention is very important for companies to maintain employee work which is influenced by job satisfaction, career development with also the non-physical work environment. This research aims to determine the effect of job satisfaction on employee retention at PT. Bali Utama Cakrawala, knowing the influence of career development on employee retention at PT. Bali Utama Cakrawala, knowing the influence of the non-physical work environment on employee retention at PT. Bali Utama Cakrawala, knowing the independent variables that have a dominant influence on employee retention at PT. Bali Utama Cakrawala. The research method used is a quantitative method with a sample size of 75 employees. The sample sampling technique is saturated. The analysis techniques used are validity and reliability tests, classical assumption tests, multiple linear regression analysis, t tests with also beta coefficients. The results of this research show the regression equation model Y = 6.978 + 0.364X1 + 0.298X2 + 0.212X3. The results of this research, it can be concluded that job satisfaction has a positive influence on employee retention at PT. Bali Utama Cakarawala, career development has a positive influence on employee retention at PT. Bali Utama Cakarawala, the non-physical work environment has a positive influence on employee retention at PT. Bali Utama Cakawala, the job satisfaction variable has a dominant influence on employee retention (Y) at PT. Bali Utama Cakawala, this can be seen from the standardized coefficient beta value of 0.460, the career development variable (X2) of 0.278, and the non-physical work environment variable (X3) of 0.235. The implication of this research is that companies need to pay attention to factors in designing policies with also programs that can increase employee retention, consisting of indicators of job satisfaction, career development and non-physical work environments.